Kinetic study of DNA hybridization on DNA-modified gold nanoparticles with engineered nano-interfaces1. Issue 93 (11th October 2015) - Takashima, Akari; Oishi, Motoi
<x xml:space="preserve">Abstract</x> We report a systematic study of DNA hybridization kinetics on GNPs with probe DNA and different molecular weight PEGs, and protruding structure of probe DNA from the PEG layer is the key factors for DNA hybridization on GNPs.